Longer-term neurological and endocrine/metabolic conditions in the deepwater horizon oil spill coast guard cohort study: A principal component analysis - Hristina Denic-Roberts; Jordan McAdam; Lawrence S. Engel; Jeanine M. Buchanich; Rachel G. Miller; Evelyn O. Talbott; Dana L. Thomas; Glen A. Cook; Blake Hansen; Jill E. Emerick; Tina Costacou; Jennifer A. Rusiecki (International Archives of Occupational and Environmental Health, 2026)
Purpose Deepwater Horizon oil spill (DWHOS) responders potentially experienced multiple stressors. We examined associations between DWHOS deployment-related stressor patterns and neurological and endocrine/metabolic conditions among U.S. Coast Guard active duty responders who completed post-deployment surveys (n = 3102). Methods Deployment-related stressor patterns were identified using principal component analysis of self-reported stressors. Neurological and endocrine/metabolic outcomes were classified from military health encounter records. Associations between principal components (PCs) and incident outcomes (2010–2015) were estimated through Cox proportional hazards regression. Results A five-component solution explained 79.2% of the variance. PC1 (high physical/moderate chemical stressor pattern) was associated with migraine [adjusted hazard ratio (aHR): 1.25, 95% confidence interval (CI): 1.01–1.56]. PC2 (high crude oil/dispersant stressor pattern) was associated with several migraine/headache conditions including migraine with aura (1.54, 1.14–2.07), mononeuritis of upper limb and mononeuritis multiplex (1.36, 1.11–1.68), disorders of lipid metabolism (1.11, 1.01–1.23 ) and its subcategory other and unspecified hyperlipidemia (1.11, 1.01–1.24), and dysmetabolic syndrome X (1.74, 1.19–2.54). PC3 (high fatigue/moderate chemical inhalation stressor pattern) was associated with several migraine/headache conditions (aHR range: 1.18–1.60), disorders of lipid metabolism (1.11, 1.00–1.23) including other and unspecified hyperlipidemia (1.13, 1.01–1.26) , and overweight and obesity (1.13, 1.00–1.27). PC4 (high anxiety/modest fatigue stressor pattern) was associated with abnormality of gait (1.34, 1.03–1.73). PC5 (high back pain) was associated with mononeuritis of lower limb, several balance and gait-related conditions , thyroid disorders, and obesity (aHRs range: 1.16–1.67). Conclusion Oil spill response stressor patterns were associated with increased risks of multiple longer-term neurological and endocrine/metabolic conditions, with associations varying by PC.